Evaluating a central bank's recent forecast failure - Ragnar Nymoen (University of Oslo, Department of Economics, 2005)
Failures are not rare in economic forecasting, probably due to the high incidence of shocks and regime shifts in the economy. Thus, there is a premium on adaptation in the forecast process, in order to avoid sequences of forecast failure. This paper evaluates a sequence of inflation forecasts in the Norges Bank Inflation Report, and we present automatized forecasts which are unaffected by forecast failure. One conclusion is that the Norges Bank fan-charts are too narrow, giving an illusion of very precise forecasts. The automatized forecasts show more adaptation once shocks have occurred than is the case for the official forecasts. On the basis of the evidence, the recent inflation forecast failure appears to have been largely avoidable. The central bank's understanding of the nature of the transmission mechanism and of the strenght and nature of the disinflationly shock that hit the economy appear to have played a major role in the recent forecast failure.
Keywords: C32; C53; E37; E44; E47; E52; E58; 330; Inflation forecasts; Monetary policy; Forecast uncertainty; Fan-charts; Structural change; Econometric models; Zentralbank; Inflation; Prognose; Prognoseverfahren; Kritik; Norwegen; Statistischer Fehler